An Analysis The Third Semester Students’ Competence in Using Adverb of Frequency at English Department Muhammadiyah University of North Maluku - faujia umasugi (EDU Journal - English Department of UMMU Journal, 2021)
Abstract: The purpose of this research was to analyzed the third semester students’ competence in using adverb of frequency in sentences. An analysis of the test was to know what extend the students’ competence in using adverb of frequency. This research used the qualitative descriptive. The subjects of the research was third semester students of English Department at Muhammadiyah University of North Maluku,the place located in Sasa south Ternate. There were 20 students as the respondents. In collecting data, the researcher making a test item in form multiple choice consist of 20 questions and asked the permission to the English lecturer and student to join the research. The instrument of research used multiple choice related to adverb of frequency. Then, the researcher analyzed the data used percentage. The research finding showed that the average score of the students’ competence in using adverb of frequency was 52. It showed that students still lack understand about adverb of frequency in sentences, especially students confused to differentiate adverb of frequency such as words “never, ever,often, occasionally and hardly ever”. The result of the test showed that the third semester students’ competence in using adverb of frequency is poor category. Key words: Students’ Competence, Adverb of Frequency